2021
DOI: 10.1002/srin.202100311
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long‐Term Ageing on Microstructural Properties and Laves Phase Precipitation of Welded P91 and P92 Steels

Abstract: Creep resistant 9% Cr steels are frequently used in civil engineering projects of supercritical coal‐fired power plants operating at temperatures of superheated steam around 610 °C. This work focus on analysis of microstructure degradation and degradation of mechanical properties of orbital narrow‐gap welding of P91 and P92 steels. Nowadays welding technology of orbital narrow‐gap using tungsten inert gas is not limited to welding of high‐pressure steam pipelines. This method is highly productive and efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In numerous published works [7][8][9][10][11][12][13][14], the degradation of mechanical properties (especially creep strength and impact toughness) of P/T92 steel was primarily ascribed to the Laves phase precipitation and coarsening. Detailed microstructural analyses, e.g., in [10][11][12][13][14][15][16], confirmed that the Laves phase very often precipitates on the Cr 23 C 6 -based carbides, which serve as preferential sites for the Laves phase nucleation. Some authors, e.g., [17][18][19][20], revealed positive effects of fine Laves phase particles on creep resistance of high-chromium boiler steels in the early stages of their high-temperature exposure.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In numerous published works [7][8][9][10][11][12][13][14], the degradation of mechanical properties (especially creep strength and impact toughness) of P/T92 steel was primarily ascribed to the Laves phase precipitation and coarsening. Detailed microstructural analyses, e.g., in [10][11][12][13][14][15][16], confirmed that the Laves phase very often precipitates on the Cr 23 C 6 -based carbides, which serve as preferential sites for the Laves phase nucleation. Some authors, e.g., [17][18][19][20], revealed positive effects of fine Laves phase particles on creep resistance of high-chromium boiler steels in the early stages of their high-temperature exposure.…”
Section: Introductionmentioning
confidence: 88%
“…In order to differentiate between coarse Cr 23 C 6 -based carbides and Fe 2 W-based Laves phase, SEM visualizations were performed using back-scattered electrons (BSEs) contrast, which is highly sensitive on the average atomic number of a phase. This SEM/BSE technique has also been widely used by several other authors, e.g., [16][17][18][19], in order to identify reliably the Laves phase precipitates in 9 wt.% Cr steels. The corresponding SEM micrographs are shown in Figures 3b, 4b, and 5b.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…During long-term creep, the microstructure of the material will change, and new phases, such as the Laves phase (Fe, Cr) 2 (W, Mo), primarily precipitate at the boundaries of primary austenite grains, subgrains and martensite laths [2][3][4][5]. The finely dispersed Laves phase has a precipitation-strengthening effect on the matrix, which can prevent the recovery of martensitic slats and dislocations [6][7][8]. However, Abe et al [9,10] found that the precipitation of the Laves phase led to a decrease in the creep rate, but when the size of the Laves phase began to increase significantly, the creep rate increased after reaching the minimum creep rate.…”
Section: Introductionmentioning
confidence: 99%
“…Weldments of P92 steel offer poor mechanical properties at room temperature due to the formation of brittle fresh martensite in the weld fusion zone (WFZ). Other factors, including heterogeneous microstructure formation along weldments, the evolution of residual stresses along weldments, the formation of soft δ ferrite patches, the presence of diffusible hydrogen and the hardening of coarse-grained HAZ are also considered major causes of failure in P92 weldments [16,[19][20][21][22][23][24][25]. Heterogeneity in the microstructure as a result of high heat input mainly leads to variation in mechanical properties, i.e., hardness and impact toughness.…”
Section: Introductionmentioning
confidence: 99%